Anecdotes in admission interviews - Grisel Sonia Salmaso (Calidoscópio, 2010)
This paper is part of a project called MOdEAS that aims at creating a model of the Admission Interviews (AIs) in Public Mental Health carried out in Youth Centres of Mendoza Province, Argentina. My study focuses on the Narrative Instances (NIs) that are part of the AIs. The categories of NIs that I apply in my study ―Narrations (Labov, 1972) and Recounts, Anecdotes, Exempla and Observations (Plum, 2004; Martin and Rose, 2008)― have been developed by using  written narrative texts or oral ones but induced. The NIs of the AIs are, on the contrary, spontaneous and coproduced. As a consequence, it is necessary to make changes in the aforementioned categories of narratives so that they suit the spontaneous and coproduced orality of the NIs of my corpus. Therefore, the purpose of the first stage of my research project is to redefine the narrative categories so that they can be applied to the analysis of the NIs of the AIs. In Salmaso (2009) I redefined the category Recount; in this paper I provide a definition of Anecdotes. For the Anecdotes I propose (i) changes in the schematic structure through (a) the inclusion of the constituents ‘abstract’, ‘record of events’, ‘interpretation of the reaction’ and ‘reorientation’; (b) a change in nomenclature from ‘extraordinary event’ to ‘disruption’ in order to use the same label for this element in the different categories of NIs since it has the same function in all of them; (c) a redefi nition of the function of the ‘reaction’ and ‘coda’; and I also claim that (ii) due to the presence of an ‘interpretation of the reaction’, the purpose of the Anecdotes is to show the reaction of a participant/narrator to a disruption and to interpret such reaction. Key words: admission interviews, narrative instances, anecdotes, schematic structure.